2010
DOI: 10.3109/09553002.2010.501840
|View full text |Cite
|
Sign up to set email alerts
|

Purple sweet potato pigments protect murine thymocytes from60Co γ-ray-induced mitochondria-mediated apoptosis

Abstract: Pre-treatment with PSP pigments significantly inhibited ⁶⁰Co γ-ray-induced mitochondria-mediated apoptosis. This radioprotective effect might be related to ROS scavenging, the enhancement of the activity of antioxidant enzymes, the maintenance of mitochondrial transmembrane potential, and the sequential inhibition of cytochrome c release and downstream caspase and PARP cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The cell viability assays showed that 60 Co γ-ray irradiation inhibited the cell survival and PSP pigments enhanced the cell viability in a dose-dependent manner without causing cytotoxicity when applied in their optimum doses. The results were in line with our previous study [15] and further demonstrated the radioprotective effects of PSP pigments. Following exposure to irradiation, a cell-specific program of apoptosis will be engaged.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The cell viability assays showed that 60 Co γ-ray irradiation inhibited the cell survival and PSP pigments enhanced the cell viability in a dose-dependent manner without causing cytotoxicity when applied in their optimum doses. The results were in line with our previous study [15] and further demonstrated the radioprotective effects of PSP pigments. Following exposure to irradiation, a cell-specific program of apoptosis will be engaged.…”
Section: Discussionsupporting
confidence: 82%
“…There has been limited information about the radioprotective effects of PSP pigments. In our previous study we have found that PSP pigments could inhibit the 60 Co γ-ray-induced apoptosis in murine thymocytes by mitochondrial way [15]. In the present study, we further investigated the effect of PSP pigments on the apoptosis induced by 60 Co γ-ray irradiation and the roles of ROS, p53 and Bcl-2 family members involved in.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation